Executive compensation and firm performance in New Zealand: The role of employee stock option plans - David K. Ding; Ya Eem Chea (Journal of Risk and Financial Management, 2021)
We examine the role of employee stock option plans (ESOPs) in mitigating agency problems in New Zealand firms. We find that ESOPs have a significant and positive effect on firm performance relative to their non-ESOP counterparts. This relation appears within a year from the first ESOP announcement, and for two to four years after the announcement. Our results show that ESOPs improve corporate performance by 10 times the cost of the ESOPs' adoption in the first year of issue. The improvement persists for four years after the first issuance. These findings confirm the effectiveness of employee stock option plans for companies issuing ESOPs compared with companies that do not issue ESOPs, and show how much the value creation of ESOPs contributes to these firms.
Keywords: 330; employee stock option plans; executive compensation; firm performance; New Zealand